The extraordinary thermal stability of EstA from S. islandicus is independent of post translational modifications. (13th July 2017) - Stiefler‐Jensen, Daniel; Schwarz‐Linnet, Troels; de Lichtenberg, Casper; Nguyen, Tam T. T. N.; Rand, Kasper D.; Huang, Li; She, Qunxin; Teilum, Kaare
Abstract: Enzymes from thermophilic and hyper‐thermophilic organisms have an intrinsic high stability. Understanding the mechanisms behind their high stability will be important knowledge for the engineering of novel enzymes with high stability. Lysine methylation of proteins is prevalent in Sulfolobus, a genus of hyperthermophilic and acidophilic archaea. Both unspecific and temperature dependent lysine methylations are seen, but the significance of this post‐translational modification has not been investigated. Here, we test the effect of eliminating in vivo lysine methylation on the stability of an esterase (EstA). The enzyme was purified from the native host S. islandicus as well as expressed as a recombinant protein in E. coli, a mesophilic host that does not code for any machinery for in vivo lysine methylation. We find that lysine mono methylation indeed has a positive effect on the stability of EstA, but the effect is small. The effect of the lysine methylation on protein stability is secondary to that of protein expression in E. coli, as the E. coli recombinant enzyme is compromised both on stability and activity. We conclude that these differences are not attributed to any covalent difference between the protein expressed in hyperthermophilic versus mesophilic hosts.